SUFISM-BASED MORAL EDUCATION OF KH. SALEH DARAT AND KH. NAWAWI AL-BANTANI AND THE DIGITIZATION FLOW IN THE SOCIETY 5.0 ERA - Abitolkha, Amir Maliki (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2022)
Abstract: Human life is now entirely sophisticated, but at the same time simple, and fast due to digitization. However the development of the digital era unfortunately seem to neglect spiritual and moral values, as well as setting aside social vices. Therefore, this bibliographic study ascertains that Sufism-based moral education, pioneered by KH. Saleh Darat and KH. Nawawi al-Bantani, enumerate a process of purifying the heart from all impurities and fostering oneself with noble character, good behaviour, and deeds. This concept is very significant to the standard of living the modern generation, which has lost many moral, spiritual, and social values. To address this behavioural degeneracy, this concept is suggested as an alternative solution. Therefore, Sufism-based moral education displays a strategic step to address human vices in response to this twenty-first century era. Keywords: Islamic education, moral, Sufism, Saleh Darat, Nawawi al-Bantani